Analisis Penyelenggaraan Sekolah Inklusi di SDN Sukasari 5 - Nurfadhillah, Septy; Sulistiyani, Putri Salsabilla; Adawiyah, Robiatul (TSAQOFAH, 2022)
This study aims to analyze the implementation of inclusive schools at the elementary school level, observe the learning process in the classroom, the handling carried out by special teachers for children with special needs (ABK) and the availability of facilities to support the learning process of children with special needs (ABK) at SDN Sukasari 5 Kota. Tangerang. In this research, the type of research used is descriptive qualitative research. Sources of data obtained from classroom teachers and teachers who specifically handle children with special needs (ABK). Data collection techniques used in this study are through interviews, observation, and documentation. The results of this study are that the implementation of inclusive education at SDN Sukasari 5 Tangerang City has been running quite well, but not optimally. The curriculum used in inclusive learning follows the same as other general students, except for inclusive education teachers using the PPI (Individual Learning Program) curriculum and for classroom teachers using a modified curriculum. For the types of students with special needs at SDN Sukasari 5, Tangerang City, there are four students, namely there are two ADHD students, one student with mild mental retardation and one has not been diagnosed with the ABK category. The schedule for inclusive learning at this school is on Mondays and Thursdays. The school provides supporting facilities and infrastructure for the inclusive learning process, it's just that it is not as complete as in the hospital but is sufficient to support the learning process. And schools already have special teachers to handle/teach children with special needs (ABK) where the handling of children with special needs (ABK) tends to be different from other students. But the special room facilities for inclusive learning are still not optimal because the room is still joined to another room.